Organic agriculture in Africa: a source of innovation for agricultural development - De Bon, Hubert; Temple, Ludovic; Malézieux, Eric; Bendjebbar, Pauline; Fouilleux, Eve; Silvie, Pierre (Perspective, 2018)
Version française de l'article In Africa, official statistics contain little data on organic agriculture, even though its products are increasingly available on local and export markets. African consumer demand is growing, providing a dynamic economic opportunity. Today, there is no doubt that organic agriculture is making an important contribution to the agro-ecological transition process underway in Africa. It reduces the adverse environmental and health impacts of agriculture, particularly because it uses no synthetic chemical inputs. It improves the resilience of agricultural systems. Under certain conditions, its specific techniques can increase agricultural productivity, even if its yields are on average lower than those in conventional agriculture. Organic systems are labour-intensive, and as such can be a source of employment for young people in rural areas. Some scientific studies and the initiatives undertaken by many local actors confirm the importance of organic agriculture in this continent. Agricultural research now needs to support its emergence, in a context in which very few studies have so far been conducted on this subject. To ensure these fledgling initiatives develop, research could also contribute to appropriate public policy making at different levels.